Implementasi Kebijakan Penataan Ruang Terbuka Hijau Publik di Kota Semarang - Iqbal Nurhanafi; Hartuti Purnaweni; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The condition of Public Open Green Space in Semarang City has only reached 7.5% of the area of the city, althuogh as mandated by the Act every city must have a minimum 20% Open Green Space. This study describe the implementation Semarang municipal Regulation Number 14 Year 2011 on Reginal Spatial Plan and Number 7 Year 2010 on Open Green Space Planning. The purpose of this study was to see the Implementation of Open Green Space Planning in Semarang City is and to determine the proponent and obstacle factors. This research was qualitative descriptive, with informant from Semarang municipal City Planning office as well as from Park and Cleanlines office. The result of the study showed that the implementation of open green space planning in Semarang City consist of planning, utilizing and controlling. There are the obstacle factors for open green space in Semarang City, namely the high too land price, the human resources competence, uneficient communication inter agency, and awarness of society on the needs of public open green space. Semarang Municipal Goverment is suggested to achieve ‘short-term- target of 20% public Open Green Space area, to negotiate the price of land with societies, to provide training on the implementation of Open Green Space, to make the flexible coordination rules, and to give information on the Open Green Space to the society and to create activities to increase the society participation in implementing open Green space planning in Semarang.